STUDENTS’ PERSPECTIVES OF ACTIVE TEACHING-LEARNING METHODOLOGIES IN HEALTH EDUCATION - Matos, Luiz Eduardo Oliveira (2023)
The Active Teaching-Learning Methodologies (ATLM) are curricular innovation strategies that focus on student protagonists. This study aimed to investigate the ATLM from the perception of students in the health area. This  is  a  cross-sectional  study,  with  an  descriptive,  and  quantitative  approach  carried  out  through  semi-structured questionnaires distributed to students from eight courses at Federal University of Sergipe, Lagarto Campus, from February 2018 to June 2019. Data were analyzed descriptively using Excel (Microsoft®) and STATA software. 412 (25%) students participated in this research, (77%; n=317) reported that at least one of the modules with ATLM should have another teaching methodology, 42,5% (n=175) was in the common/basic cycle (1st cycle), and 30,3% (n=122) said that they would probably or change their course; 25,1% (n=102) reported that they would probably or change educational institutions. The results showed different perceptions about ATLM in higher education, indicating the importance of further studies on pedagogical practices in health education. In the analysis of the curricular module, the Tutorial module that uses Problem Based Learning was identified as the one that most influences the generation of tension, anxiety, and stress. The PEC module based on problematization influenced more aspects of Humanization and Criticality. Skills were characterized as the most diverse module in ATLM, with the highest prevalence of high flow for professional training. The results can be different about the ATLM in higher education. Generally indicating the importance of further studies on pedagogical practices in health education and the need for institutional and teaching reflection on the applicability of the ATLM.